Measurement of Economic Welfare Risk and Resilience of the Philippine Regions - Rio Yonson; Ilan Noy (Center for Economic Studies and ifo Institute (CESifo), 2018)
Using an economic model to assess welfare risk and resilience to disasters, this paper systematically tackles the questions: 1) How much asset and welfare risks does each region in the Philippines face from riverine flood disasters? 2) How resilient is each region to riverine flood disasters? and 3) What are the available interventions per region to strengthen resilience to riverine flood disasters and what will be their measured benefit? We study the 18 regions of the Philippines to demonstrate the channels through which macroeconomic asset and output losses from disasters translate to consumption and welfare losses at the microeconomic level. Apart from the prioritization of regions based on resilience and welfare risk, we identify a menu of policy options ranked according to their level of effectiveness in increasing resilience and reducing welfare risk from riverine floods. While there are similarities in the ranking of policies among regions with comparable levels of resilience and welfare risk, the ranking of priorities varies for different regions. This suggests that there are region-specific conditions and drivers that need to be integrated into policies and development processes so that these conditions are effectively addressed. Overall, the results indicate that reduction of adverse disaster impacts, including welfare losses, and reduction of poverty are generally complementary.
Keywords: Q54; 330; disasters; floods; risk; resilience; floods; Philippines